Pelatihan Perkoperasian Anggaran Dasar (AD)/Anggaran Rumah Tangga (ART) Koperasi bagi Pengelola Koperasi se Jawa Barat - Setiawati, Rosti (LPPM Universitas Koperasi Indonesia, 2024)
Guidelines which contain binding rules and regulate the activities of cooperative members in running their organization are included in the Cooperative's Articles of Association and Bylaws. Important regulations that form the basis of other regulations for a cooperative are called the Cooperative's Articles of Association, while those that become the implementing regulations of the Cooperative's Articles of Association are called the Cooperative's Bylaws. The AD/ART involves setting up work mechanisms within the organization, providing a detailed explanation of the structured life of the Cooperative organization and functioning as the main guideline for every business, management, financial and technical aspect of the Cooperative organization for the Management, Supervisors, Managers and all members. Cooperative. The Cooperative's AD/ART contains provisions that will become the basis for the life of a Cooperative organization. The Cooperative's AD/ART is a guideline for the Management, Supervisors, Managers and members of the Cooperative. Anyone who is involved in a Cooperative must follow the guidelines in the Cooperative's AD/ART. Therefore, the Cooperative AD/ART is the main guideline for running a Cooperative organization, which contains regulations for all Cooperative members in carrying out their activities.